The eyes & the impossible - Eggers, Dave; Harris, Shawn (Artist) (New York : Alfred A. Knopf, 2023)
Free dog Johannes' job is to observe everything that happens in his urban park and report back to the park's three bison elders, but changes are afoot, including more humans, a new building, a boatload of goats, and a shocking revelation that changes his view of the world.
Booklist starred, February 2023
Pub Weekly, March 2023
Kirkus Starred, March 2023
4.7
3-6
790L
Keywords: Dogs -- Juvenile fiction; Animals -- Juvenile fiction; Parks -- Juvenile fiction; City and town life -- Juvenile fiction; Friendship -- Juvenile fiction; Dogs -- Fiction; Animals -- Fiction; Parks -- Fiction; City and town life -- Fiction; Friendship -- Fiction; Animal fiction